O supremo tribunal federal e o alcance da lei da anistia: As disputas de um processo inconcluso - Gedoz, Cassiano (Universidade do Vale do Rio dos Sinos, 2013)
In 2008, the Lawyers Association of Brazil (LAB) filed in the Supreme Federal Bound Tribunal (SFBT) an Argumentation of Noncompliance of Fundamental Precept (ANFP 153), in which it was questioned the consolidated interpretation of the 1st article of the1st paragraph of the Amnesty Law number 6.683, from August 28th, 1979. In that, the amnesty is defined to be reciprocal, being amnestied, in this way, also, the representatives of the Brazilian State who committed crimes of torture, death and people disappearance during the Military Dictatorship period (1964-1985). The denouement of the ANFP 153 happened on April 28th and 29th, 2010, with the voting in plenary, of the LAB proposition, in which seven ministers voted against the filed action, and two of them voted in favor of it – making the law of 1979 unchanged for the required effects – among them, the possibility of judgment of the perpetrated crimes during the exception regime. In this research, we behold the ADF 153, bringing into focus the historical analysis, starting with those who were involved on the manifestations. The judgment demonstrates that it does not interact only with Juridical questions, but the historical past was a constantly object to debate. Mainly, in Ministers’ votes that rejected the action. The attempt of OAB, while proposing the reinterpretation of the Annesty Law based on the effectives ones, was requesting the penal executions for those who committed the torture, death and disappearances crimes during the Military Dictatorship Period. Otherwise this attempt found a remarkable past contest during the arguments judgment. T\he most manifestations were used historical reasons. Constantly leading people involved to appropriation and fights around past memory, in a process which juridical, social, politics and historical matter’s scopes gets in confluence.
Keywords: Ditadura civil-militar; Anistia; Ordem dos Advogados do Brasil; Supremo Tribunal Federal; Civil-military dictatorship; Amnesty; Federal Supremacy Court; ACCNPQ::Ciências Humanas::História